Staphylococcus epidermidis adhesion on modified urea/urethane elastomers - Teixeira, P. (2006)
Block urea/urethane co-polymer films present elastomeric properties with the possible tuning of their surface properties within a wide range and are therefore considered relevant surfaces for possible medical applications. In particular, thin free standing films of urea/urethane elastomers with two soft segments, polypropylene oxide and more hydrophobic polybutadiene, develop multistable states with surface topography features with remarkable regularity. Moreover, complex surface structures may be obtained by UV radiation treatment followed by suitable mechanical action and also by extraction of the elastomer with a suitable solvent. In the present work, different modified elastomer samples were assayed for Staphylococcus epidermidis adhesion during 2 h and the extent of bacterial adhesion was evaluated by automatic cell enumeration. Bacterial adhesion assays demonstrate that the typical trend relating the increase in the number of adhered bacteria with the increase of the surface roughness does not hold for all materials. Results may be interpreted taking into account both the surface topography and the different types ofmicro-phase segregation of hydrophobic and hydrophilic parts of the elastomer.